Tinjauan Ekonomi Islam Terhadap Kelayakan Usaha Cabai Merah (Studi Kasus Di Desa Duriasi Kabupaten Konawe) - Leni Saleh (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
The purpose of this research is to know : (1) The feasibility of red chili pepper in Duriasi village of Konawe regency, and (2) Economic review of Islam to the feasibility of red chili pepper in Duriasi village Konawe regency. The method of determining the sample is purposive. Sampling in this research is conducted by census that is take all population of red chili pepper farmer so that total of respondent is 20 respondents. Result of research concluded that : (1) Based on analysis result obtained R/C equal to 3,06. The value of R/C > 1, this means that in the red chili pepper plant undertaken by farmer of respondents in the village Duriasi subdistrict Wonggeduku is efficient or feasible to cultivate and every one rupiah issued will generate revenue of 3,06 rupiah. (2) According to the Islamic economic review of the feasibility of red chili pepper business is accordance with Islamic ekonomic principles because it can realize the level of welfare and increase the level of economic income of family members, especially farmers.